The Treatment of Deep Vein Thrombosis in the Pelvis and Leg - Hach-Wunderle, Viola (Deutscher Arzte Verlag, 2008)
INTRODUCTION: Deep vein thrombosis is associated with a risk of pulmonary embolism and post thrombotic syndrome (PTS). METHODS: Selective literature review with special reference to the American College of Chest Physicians’ current guidelines and the German S2 interdisciplinary guideline. RESULTS AND DISCUSSION: The most important therapeutic measure is prompt and adequate anticoagulation with heparin or fondaparinux. Thrombolysis or thrombectomy is only indicated in highly selected severe cases. The risk of PTS can be reduced by immediate ongoing treatment with compression stockings. Prevention of relapse is achieved using vitamin K antagonists with a target INR of 2.0 to 3.0. The duration of anticoagulation should be tailored to the localisation and etiology of the thrombosis, from at least three months to indefinite treatment. The ongoing risk of bleeding secondary to anticoagulation should be reevaluated at regular intervals as a cost-benefit analysis. New anticoagulants for acute and long term treatment will soon be available for clinical use.